Drug-eluting balloon versus standard percutaneous transluminal angioplasty in infrapopliteal arterial disease: A meta-analysis of randomized trials. (November 2016) - Wu, Ridong; Tang, Shi; Wang, Mian; Li, Zilun; Yao, Chen; Wang, Shenming
Abstract: Background: Drug-eluting balloon (DEB) and standard percutaneous transluminal angioplasty (PTA) are commonly used endovascular therapeutic procedures for the revascularization of infrapopliteal arterial occlusive disease. However, which procedure is more beneficial for patients is unknown. Methods and results: We performed a meta-analysis, searching PubMed, EMBASE, the Cochrane Central Register of Controlled Trials, ISI Web of Knowledge, and relevant websites without language or publication date restrictions for randomized trials that compared DEB with PTA in patients with infrapopliteal arterial occlusive disease. The keywords were "drug-eluting balloon, " "angioplasty, " "infrapopliteal, " "tibial arteries, " and "below the knee". We selected late lumen loss, target lesion revascularization, binary restenosis, major adverse event as the outcomes of this meta-analysis. Based on the inclusion criteria, we identified 4 prospective randomized trials. One-year outcomes did not show any significant differences between the DEB and PTA groups, respectively: target lesion revascularization (14.6% versus 22.1%; OR, 0.71; 95% CI, 0.45–1.14, P = 0.15), binary restenosis (33.3% versus 62.9%; OR, 0.40; 95% CI, 0.04–3.73, P = 0.42), late lumen loss (MD, −0.52; 95% CI, −1.52 to 0.48, P = 0.31), major adverse event (29.0% versus 38.8%; OR, 0.68; 95% CI, 0.24–1.95, P = 0.48). Conclusions: For infrapopliteal arterial occlusive disease, DEB has the same one-year benefits as PTA. There is insufficient evidence to support the superiority of either method. Further large-scale prospective randomized trials should produce more reliable results. Highlights: A comprehensive literature review and quantitative analysis were conducted. For infrapopliteal arterial occlusive disease, DEB had the same one-year benefits as PTA. There was insufficient evidence to support the superiority of either method. Large-scale prospective randomized trials made more reliable results.